Effectiveness of reminders to sustain practice change among direct care providers in residential care facilities: a cluster randomized controlled trial. - Slaughter, Susan E.; Eliasziw, Misha.; Ickert, Carla.; Jones, C. Allyson.; Estabrooks, Carole A.; Wagg, Adrian S. (Tufts University. Tisch Library., 2020)
Keywords: Cluster randomized controlled trial, Sustainability, Reminders, Sit-to-stand activity.; Springer Open.